A high-sulfur-resistant co catalytic combustion catalyst, its preparation method and application
Patent Information
- Application Number
- CN202611419488.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-16
AI Technical Summary
然而,该催化剂的活性组分仅为单一的铂,载体为TiO2-SiO2二元复合氧化物,在高浓度SO2(如3000ppm) 条件下,其抗硫性能和稳定性仍存在不足,难以满足工业高硫烟气的净化需求
[0017]本发明提供了上述技术方案所述的抗高硫的CO催化燃烧催化剂的制备方法。本发明通过共沉淀法得到ZrO2-WO3-Sm2O3-SiO2复合氧化物载体,再通过共浸渍法将活性组分和助催化剂负载于载体上,然后用酸处理将BaO转化为BaSO4。本发明提供的方法采用浸渍法,催化剂各组分分散度较高,活性位较多,且具有步骤简单,操作方便,成本低廉的优势,适宜工业化生产。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst technology, specifically relating to a high-sulfur-resistant CO catalytic combustion catalyst, its preparation method, and its application. Background Technology
[0002] Carbon monoxide (CO) is an air pollutant widely found in industrial flue gas, and excessive emissions can cause serious harm to the atmospheric environment and human health. The steel industry is one of the main sources of CO emissions in my country, with processes such as sintering, pellet roasting, and blast furnace ironmaking generating large amounts of CO-containing flue gas. Statistics show that the CO concentration in typical steel sintering flue gas often reaches 5000-8000 mg / m³. 3 In addition, CO emissions also exist in industrial sectors such as coking, chemical processing, and cement kilns, becoming an indispensable part of air pollution control. Catalytic oxidation technology is considered a stable and efficient purification method for CO emission control.
[0003] Supported noble metal catalysts (such as Pt, Pd, Au, and Ru) have shown broad application prospects in this field due to their excellent low-temperature oxidation activity and resistance to water and sulfur. However, industrial flue gas has a complex composition, and in addition to CO, it commonly contains toxic components such as sulfur dioxide (SO2), which cause irreversible poisoning to CO oxidation catalysts, leading to severe catalyst deactivation. Even after desulfurization treatment, a certain amount of SO2 remains in the sintering flue gas. This residual SO2 adsorbs, oxidizes, and transforms into sulfate species on the catalyst surface, covering active sites or blocking support pores, resulting in a significant decrease in catalytic activity or even complete deactivation. Studies have shown that SO2 exposure not only leads to sulfidation of noble metal active sites but also forms sulfate deposits on the support surface, fundamentally destroying the catalytic function of the catalyst. How to maintain high activity and long lifespan of CO oxidation catalysts in high-sulfur environments has become a core problem that urgently needs to be solved in the field of environmental catalysis.
[0004] Chinese patent CN117085678A discloses a supported platinum catalyst using a TiO2-SiO2 composite oxide as a support and BaSO4 and Sm2O3 as modifying agents to support the platinum active component. This catalyst exhibits certain sulfur resistance under sulfur-containing atmosphere (50 ppm). However, since the active component of this catalyst is only platinum, and the support is a TiO2-SiO2 binary composite oxide, its sulfur resistance and stability are still insufficient under high-concentration SO2 conditions (e.g., 3000 ppm), making it difficult to meet the purification requirements of high-sulfur industrial flue gas. Summary of the Invention
[0005] In view of this, the present invention provides a high-sulfur-resistant CO catalytic combustion catalyst, its preparation method, and its application. The CO catalytic combustion catalyst prepared by the present invention can significantly improve the catalyst's resistance to high sulfur while maintaining high CO oxidation activity, providing a practical and feasible technical route for the efficient purification of CO under high-sulfur flue gas conditions.
[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a high-sulfur-resistant CO catalytic combustion catalyst, comprising a strongly acidic support, an active component supported in the porous structure of the strongly acidic support, and a co-catalyst; The cocatalyst includes BaSO4 and Sm2O3; the active component is a composite active component of Pt and V2O5; the strong acid support is a ZrO2-WO3-Sm2O3-SiO2 quaternary composite oxide; The total mass of the active components Pt and V2O5 is 1% to 8% of the mass of the CO catalytic combustion catalyst.
[0007] Preferably, the content of the strong acid support is 60% to 89% by mass percentage, the content of the co-catalyst is 2% to 35%, the content of the active component is 1% to 10%, and the sum of the mass percentages of the strong acid support, co-catalyst, and active component is 100%.
[0008] Preferably, the ZrO2-WO3-Sm2O3-SiO2 composite oxide contains 30%~50% ZrO2, 20%~40% WO3, 5%~20% Sm2O3, and 10%~30% SiO2 by mass; the mass ratio of Pt to V2O5 in the active component is (0.1~1):(1~5).
[0009] Preferably, the particle size of the CO catalytic combustion catalyst is 20-80 mesh.
[0010] This invention also provides a method for preparing the CO catalytic combustion catalyst described in the above technical solution, comprising the following steps: (1) After mixing zirconium source, tungsten source, samarium source, silicon source, alcohol solvent and precipitant, the pH value of the resulting mixture was adjusted to 10~11 for the first deposition, aging and first calcination to obtain ZrO2-WO3-Sm2O3-SiO2 composite oxide; (2) The ZrO2-WO3-Sm2O3-SiO2 composite oxide, the aqueous solution of the active component precursor and the aqueous solution of the co-catalyst precursor are mixed and then allowed to stand, heated and mixed in the Ath, Bth, Cth and Dth stages, and then calcined to obtain the catalyst supported on the active component. (3) The supported active component catalyst and the acid solution are mixed and acid-treated to obtain a high-sulfur CO catalytic combustion catalyst.
[0011] Preferably, the zirconium source is zirconium nitrate; the tungsten source is ammonium metatungstate; the samarium source is samarium nitrate; the silicon source is tetraethyl orthosilicate; the alcohol solvent is anhydrous ethanol; the first deposition temperature is room temperature and the time is 1 hour; the aging temperature is 70~90℃ and the holding time is 5~7 hours; the first calcination temperature is 500~600℃ and the holding time is 3~5 hours.
[0012] Preferably, the active component precursor includes chloroplatinic acid and / or vanadium oxalate complex; the vanadium oxalate complex is a mixed solution of oxalic acid dihydrate and ammonium metavanadate; the molar ratio of oxalic acid dihydrate to ammonium metavanadate in the mixed solution of oxalic acid dihydrate and ammonium metavanadate is 2~4:1; the cocatalyst precursor includes barium acetate dihydrate and samarium nitrate.
[0013] Preferably, the settling temperature is room temperature and the time is 1-2 hours; The heating and mixing method for the Ath heating method is heating and stirring; the heating and stirring temperature for the Ath heating and mixing is 35~45℃, the time is 0.5~1.5h, and the stirring speed is 50~150r / min; The heating and mixing method for the Bth heating and mixing is heating and stirring; the heating and stirring temperature for the Bth heating and mixing is 45~55℃; the stirring time is 0.5~1.5h; and the stirring speed is 50~150r / min. The Cth heating and mixing method is heating and stirring; the heating and stirring temperature of the Cth heating and mixing is 55~65℃, the stirring time is 0.5~1.5h, and the stirring speed is 50~150r / min; The heating and mixing method for the Dth heating and mixing is heating and stirring; the heating and stirring temperature for the Dth heating and mixing is 65~75℃, the stirring time is 0.5~1.5h, and the stirring speed is 50~150r / min; The second roasting temperature is 500~600℃, and the holding time is 3~5h.
[0014] The present invention also relates to the application of the CO catalytic combustion catalyst described herein or the high-sulfur-resistant CO catalytic combustion catalyst prepared by the above-described preparation method in CO catalytic combustion.
[0015] Preferably, during the catalytic combustion of CO, the volume concentration of SO2 in the CO reaction gas is ≥1000ppm.
[0016] This invention provides a high-sulfur-resistant CO catalytic combustion catalyst. The high-sulfur-resistant CO catalytic combustion catalyst provided by this invention consists of a composite oxide support, an active component, and a co-catalyst. The composite oxide support is strongly acidic, effectively inhibiting SO2 adsorption onto the catalyst and causing catalyst poisoning. The active component has an ultra-low mass content. The co-catalyst is BaSO4 and Sm2O3; BaSO4 effectively protects the active sites from sulfur poisoning, and Sm2O3 optimizes the catalyst's redox capacity. Through the synergistic effect between the active components, the catalyst significantly improves its high-sulfur resistance while maintaining high CO oxidation activity, thus reducing costs. The results of the examples show that at a space velocity of 20000 mL·g... -1 ·h -1 Under conditions of 0.5% CO concentration, a CO conversion rate of 90% is achieved at 220℃. After stabilizing for 200 hours in the presence of 3000ppm SO2 and at a CO conversion rate of 90%, the CO conversion rate remains unchanged. The catalyst provided by this invention has excellent catalytic activity and good resistance to high sulfur.
[0017] This invention provides a method for preparing the high-sulfur-resistant CO catalytic combustion catalyst described in the above-mentioned technical solution. The invention obtains a ZrO2-WO3-Sm2O3-SiO2 composite oxide support via co-precipitation, then loads the active component and co-catalyst onto the support via co-impregnation, and finally converts BaO to BaSO4 by acid treatment. The method provided by this invention uses an impregnation method, resulting in high dispersion of catalyst components, numerous active sites, and advantages such as simple steps, convenient operation, and low cost, making it suitable for industrial production. Detailed Implementation
[0018] This invention provides a high-sulfur-resistant CO catalytic combustion catalyst, comprising a strongly acidic support, an active component supported in the porous structure of the strongly acidic support, and a co-catalyst; The cocatalyst includes BaSO4 and Sm2O3; the active component is a composite active component of Pt and V2O5; the strong acid support is a ZrO2-WO3-Sm2O3-SiO2 quaternary composite oxide; The total mass of the active components Pt and V2O5 is 1% to 8% of the mass of the CO catalytic combustion catalyst.
[0019] In this invention, the CO catalytic combustion catalyst comprises, by mass percentage, 60% to 89% of a strongly acidic support, which may be further 62% to 80%, and more specifically 65% to 75%; the strongly acidic support is a ZrO2-WO3-Sm2O3-SiO2 quaternary composite oxide.
[0020] In this invention, the ZrO2 mass content in the ZrO2-WO3-Sm2O3-SiO2 quaternary composite oxide is 30%~50%, more preferably 35%~45%, and more preferably 38%~42%; the WO3 mass content is 20%~40%, more preferably 25%~35%, and more preferably 28%~32%; the Sm2O3 mass content is 5%~20%, more preferably 7%~15%, and more preferably 8%~12%; and the SiO2 mass content is 10%~30%, more preferably 15%~25%, and more preferably 18%~22%.
[0021] In this invention, the ZrO2-WO3-Sm2O3-SiO2 quaternary composite oxide can specifically be ZrO2-WO3-Sm2O3-SiO2. 0.4 W 0.3 Sm 0.1 Si 0.2 Composite oxides.
[0022] In this invention, the ZrO2-WO3-Sm2O3-SiO2 composite oxide serves as the support framework for the high-sulfur-resistant CO catalytic combustion catalyst, providing loading sites for the active components. It is strongly acidic and can effectively inhibit SO2 adsorption on the catalyst, thus preventing catalyst poisoning.
[0023] In this invention, the total mass of the active components Pt and V2O5 is 1% to 10% of the mass of the CO catalytic combustion catalyst, and may be further 3% to 7%, or specifically 4.5% to 5.5%.
[0024] In this invention, the CO catalytic combustion catalyst, by mass percentage, comprises 2% to 35% of a co-catalyst supported on the surface of the strongly acidic support, which may further be 10% to 30%, and preferably 15% to 20%; the co-catalyst comprises BaSO4 and Sm2O3; the mass of BaSO4 is 1% to 15% of the mass of the CO catalytic combustion catalyst, which may further be 5% to 15%, and preferably 10% to 15%; the mass of Sm2O3 is 1% to 15% of the mass of the CO catalytic combustion catalyst, which may further be 5% to 15%, and preferably 10% to 15%.
[0025] In this invention, BaSO4 in the co-catalyst serves as the main anti-sulfur agent, effectively protecting active sites from sulfur poisoning. In this invention, Sm2O3 in the co-catalyst simultaneously possesses excellent redox and anti-SO2 adsorption capabilities, improving CO conversion while assisting BaSO4 in inhibiting SO2 adsorption.
[0026] In this invention, the particle size of the CO catalytic combustion catalyst can be 20-80 mesh, more preferably 40-60 mesh.
[0027] In this invention, the sum of the mass percentages of the strongly acidic support, the co-catalyst, and the active component is 100%.
[0028] This invention also provides a method for preparing the CO catalytic combustion catalyst described above, comprising the following steps: (1) After mixing zirconium source, tungsten source, samarium source, silicon source, alcohol solvent and precipitant, the pH value of the resulting mixture was adjusted to 10~11 for first deposition, aging and first calcination to obtain ZrO2-WO3-Sm2O3-SiO2 quaternary composite oxide; (2) The ZrO2-WO3-Sm2O3-SiO2 quaternary composite oxide, the aqueous solution of the active component precursor and the aqueous solution of the co-catalyst precursor are mixed and then allowed to stand, heated and mixed in the Ath, Bth, Cth and Dth stages, and then calcined to obtain the catalyst with supported active component. (3) The supported active component catalyst and the acid solution are mixed and acid-treated to obtain a high-sulfur CO catalytic combustion catalyst.
[0029] In this invention, zirconium source, tungsten source, samarium source, silicon source, alcohol solvent and precipitant are mixed and the pH value of the resulting mixture is adjusted to 10-11 for first deposition, aging and first calcination to obtain ZrO2-WO3-Sm2O3-SiO2 composite oxide.
[0030] In this invention, the zirconium source can be zirconium nitrate; the tungsten source can be ammonium metatungstate; the samarium source can be samarium nitrate; the silicon source can be tetraethyl orthosilicate; and the alcohol solvent can be anhydrous ethanol.
[0031] In this invention, the mixing method can be stirring; the stirring speed can be 200~300 r / min, further 220~280 r / min, preferably 240~260 r / min, and the temperature can be room temperature. In this invention, the precipitant is preferably added dropwise to the aqueous solution of the zirconium source, tungsten source, samarium source, and silicon source; the dropping rate can be 30~70 drops / min, further 40~60 drops / min, preferably 50 drops / min.
[0032] In this invention, the temperature of the first deposition can be room temperature, and the time can be 1 hour.
[0033] In this invention, the aging temperature can be 70-90℃, and more preferably 75-85℃, and the holding time can be 5-7 hours, and more preferably 6 hours. In this invention, after aging, the obtained product is preferably filtered, washed, and dried sequentially; the filtration method can be suction filtration; the washing reagent can be deionized water; the number of washings is greater than 2; the drying temperature can be 70-90℃, and more preferably 75-85℃, and the holding time can be 10-20 hours, and more preferably 15 hours.
[0034] In this invention, the temperature of the first calcination can be 500~600℃, preferably 550℃, and the holding time can be 3~5h, preferably 4h.
[0035] After obtaining the ZrO2-WO3-Sm2O3-SiO2 composite oxide, the present invention mixes the ZrO2-WO3-Sm2O3-SiO2 composite oxide, the aqueous solution of the active component precursor, and the aqueous solution of the co-catalyst precursor, and then sequentially allows them to stand, heat and mix in step A, heat and mix in step B, heat and mix in step C, heat and mix in step D, and then calcines them to obtain a catalyst supported on the active component.
[0036] In this invention, the active component precursor may include chloroplatinic acid and / or vanadium oxalate complex; the mass concentration of the aqueous solution of the active component precursor may be 20 mg / mL; the vanadium oxalate complex may be a mixed solution of oxalic acid dihydrate and ammonium metavanadate; the molar ratio of oxalic acid dihydrate to ammonium metavanadate in the mixed solution of oxalic acid dihydrate and ammonium metavanadate may be 2 to 4:1, specifically 2:1, 3:1 or 4:1.
[0037] In this invention, the co-catalyst precursor may include barium acetate dihydrate and samarium nitrate; the precipitant is ammonia water, and the concentration of the ammonia water may be 0.8~1.2 mol / L, further 0.9~1.1 mol / L, preferably 1 mol / L.
[0038] In this invention, the settling temperature can be room temperature, and the time can be 1 to 2 hours, or even 1.5 hours.
[0039] In this invention, the heating and mixing method of the Ath heating method can be heating and stirring; the heating and stirring temperature can be 35~45℃, and can be further 38~42℃, the stirring time can be 0.5~1.5h, and can be further 1h, and the stirring speed can be 50~150r / min, and can be further 80~120r / min.
[0040] In this invention, the heating and mixing method of the Bth step can be heating and stirring; the heating and stirring temperature can be 45~55℃, and can be further 48~52℃, the stirring time can be 0.5~1.5h, and can be further 1h, and the stirring speed can be 50~150r / min, and can be further 80~120r / min.
[0041] In this invention, the heating and mixing method of the Cth step can be heating and stirring; the heating and stirring temperature can be 55~65℃, and can be further 58~62℃, the stirring time can be 0.5~1.5h, and can be further 1h, and the stirring speed can be 50~150r / min, and can be further 80~120r / min.
[0042] In this invention, the heating and mixing method of the Dth step can be heating and stirring; the heating and stirring temperature can be 65~75℃, and can be further 68~72℃, the stirring time can be 0.5~1.5h, and can be further 1h, and the stirring speed can be 50~150r / min, and can be further 80~120r / min.
[0043] In this invention, after the Dth heating and mixing, the resulting product is preferably dried; the drying temperature can be 70~90℃, or more preferably 75~85℃, and the holding time can be 10~20h, or more preferably 15h.
[0044] In this invention, the second calcination temperature can be 500~600℃, or more specifically 550℃, and the holding time can be 3~5h, or more specifically 4h.
[0045] After obtaining the supported active component catalyst, the present invention mixes the supported active component catalyst with an acid solution and performs acid treatment to obtain a high-sulfur-resistant CO catalytic combustion catalyst.
[0046] In this invention, the acid solution can be a dilute sulfuric acid solution with a concentration of 0.1~0.5 mol / L; the acid treatment time can be 0.5~1.5 h, and can be further 1 h; the acid treatment temperature is preferably room temperature; the acid treatment method can be stirring; the stirring speed can be 200~300 r / min, and can be further 220~280 r / min, preferably 240~260 r / min.
[0047] In this invention, after acid treatment, the resulting product is preferably filtered, washed, and dried sequentially; the filtration is preferably vacuum filtration; the washing reagent is preferably deionized water; the washing is preferably performed at least twice; the drying temperature can be 70-90°C, and can be further 75-85°C, and the holding time can be 10-20 hours, and can be further 15 hours. This invention preferably converts BaO to BaSO4 through acid treatment.
[0048] This invention also provides the application of the high-sulfur-resistant CO catalytic combustion catalyst described above or the high-sulfur-resistant CO catalytic combustion catalyst prepared by the preparation method described above in CO combustion.
[0049] In this invention, the method of application can be to place the high-sulfur-resistant CO catalytic combustion catalyst in a CO-containing gas to carry out a CO catalytic combustion reaction; the temperature of the CO catalytic combustion can be 100~300℃, and can be further 150~250℃; during the CO catalytic combustion, the volume concentration of SO2 in the CO reaction gas is ≥1000ppm.
[0050] In an embodiment of the invention, the catalyst's resistance to sulfur poisoning was verified by incorporating SO2 into the CO reaction gas, wherein the concentration of SO2 in the CO reaction gas was 3000 ppm. In a specific embodiment, the space velocity was 20000 mL·g. -1 ·h -1 The simulated standard CO reaction gas volume composition is: 0.5% CO, 5 vol% O2, N2 as balance gas, and 3000 ppm SO2.
[0051] To further illustrate the present invention, the technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0052] Zr carrier 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Weigh 2.79g zirconium nitrate pentahydrate, 0.64g ammonium metatungstate, 0.51g samarium nitrate hexahydrate, and 1.39g tetraethyl orthosilicate, mix them in 150mL of anhydrous ethanol, stir to dissolve, and obtain a mixed solution; At room temperature, 100 mL of ammonia solution (concentration of 1 mol / L) was added dropwise at a rate of 50 drops / min to the mixed solution until complete precipitation (precipitation time was 1 h). During the precipitation process, the pH was maintained at 10.5. After precipitation, the mixed solution was aged in a water bath at 80 °C for 6 h, then filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours and then calcined at 550°C for 4 hours to obtain Zr. 0.4 W 0.3 Sm 0.1 Si 0.2 Composite oxide powder (hereinafter referred to as Zr in the examples) 0.4 W 0.3 Sm 0.1 Si 0.2 powder).
[0053] Comparative carrier Zr 0.5 W 0.3 Si 0.2 Preparation: Weigh 2.79g zirconium nitrate pentahydrate, 0.99g ammonium metatungstate, and 0.54g tetraethyl orthosilicate, mix them in 150mL of anhydrous ethanol, stir to dissolve, and obtain a mixed solution; Add 100 mL of ammonia solution (concentration of 1 mol / L) dropwise to the mixed solution at a rate of 50 drops / min until complete precipitation. During the precipitation process, maintain the pH at 10.5. After precipitation, age the mixture in a water bath at 80°C for 6 hours, then filter it and wash it twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours and then calcined at 550°C for 4 hours to obtain Zr. 0.5 W 0.3 Si 0.2 Composite oxide powder (hereinafter referred to as Zr in comparative examples) 0.5 W 0.3 Si 0.2 powder).
[0054] Example 1 catalyst Pt 0.1 V3-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 3 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1), 0.1 mL of chloroplatinic acid solution (20 mg / mL), 0.0284 g of barium acetate dihydrate, and 0.051 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared Zr... 0.4 W 0.3 Sm 0.1 Si 0.2 1.898g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550°C for 4 hours to obtain Pt. 0.1 V3-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder; 2g Pt 0.1 V3-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder and 3 mL of 0.3 mol / L sulfuric acid solution were mixed and stirred at room temperature for 1 h for acid treatment. After the treatment, the mixture was filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours to obtain Pt. 0.1 V3-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 powder.
[0055] Example 2 catalyst Pt 0.3 V3-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 3 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1), 0.3 mL of chloroplatinic acid solution (20 mg / mL), 0.0284 g of barium acetate dihydrate, and 0.051 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared Zr... 0.4 W 0.3 Sm 0.1 Si 0.2 1.894g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550°C for 4 hours to obtain Pt. 0.3 V3-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder; 2g Pt1V3-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si0.2 (BaO) powder and 3 mL of 0.3 mol / L sulfuric acid solution were mixed and stirred at room temperature for 1 h for acid treatment. After the treatment, the mixture was filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours to obtain Pt1V3-Ba1Sm1 / Zr. 0.4 W 0.3 Sm 0.1 Si 0.2 powder.
[0056] Example 3 catalyst Pt 0.5 V3-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 3 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1), 0.5 mL of chloroplatinic acid solution (20 mg / mL), 0.0284 g of barium acetate dihydrate, and 0.051 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared Zr... 0.4 W 0.3 Sm 0.1 Si 0.2 1.89g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550°C for 4 hours to obtain Pt. 0.5 V3-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder; 2g Pt 0.5 V3-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder and 3 mL of 0.3 mol / L sulfuric acid solution were mixed and stirred at room temperature for 1 h for acid treatment. After the treatment, the mixture was filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours to obtain Pt. 0.5 V3-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2powder.
[0057] Example 4 Catalyst Pt1V3-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 3 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1), 1 mL of chloroplatinic acid solution (20 mg / mL), 0.0284 g of barium acetate dihydrate, and 0.051 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared Zr... 0.4 W 0.3 Sm 0.1 Si 0.2 1.88g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550℃ for 4 hours to obtain Pt1V3-Ba1Sm1 / Zr. 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder; 2g Pt1V3-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder and 3 mL of 0.3 mol / L sulfuric acid solution were mixed and stirred at room temperature for 1 h for acid treatment. After the treatment, the mixture was filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours to obtain Pt1V3-Ba1Sm1 / Zr. 0.4 W 0.3 Sm 0.1 Si 0.2 powder.
[0058] Example 5 catalyst Pt 0.5 V1-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 1 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1), 0.5 mL of chloroplatinic acid solution (20 mg / mL), 0.0284 g of barium acetate dihydrate, and 0.051 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared Zr... 0.4 W 0.3 Sm 0.1 Si 0.2 1.93g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550°C for 4 hours to obtain Pt. 0.5 V1-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder; 2g Pt 0.5 V1-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder and 3 mL of 0.3 mol / L sulfuric acid solution were mixed and stirred at room temperature for 1 h for acid treatment. After the treatment, the mixture was filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours to obtain Pt. 0.5 V1-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 powder.
[0059] Example 6 catalyst Pt 0.5 V5-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 5 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1), 0.5 mL of chloroplatinic acid solution (20 mg / mL), 0.0284 g of barium acetate dihydrate, and 0.051 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared Zr... 0.4 W 0.3 Sm 0.1 Si 0.21.85g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550°C for 4 hours to obtain Pt. 0.5 V5-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder; 2g Pt 0.5 V5-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder and 3 mL of 0.3 mol / L sulfuric acid solution were mixed and stirred at room temperature for 1 h for acid treatment. After the treatment, the mixture was filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours to obtain Pt. 0.5 V5-Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 powder.
[0060] Example 7 catalyst Pt 0.5 V5-Ba1Sm5 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 5 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1), 0.5 mL of chloroplatinic acid solution (20 mg / mL), 0.0284 g of barium acetate dihydrate, and 0.255 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared Zr... 0.4 W 0.3 Sm 0.1 Si 0.2 1.77g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550°C for 4 hours to obtain Pt. 0.5 V5-Ba1Sm5 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder; 2g Pt 0.5 V5-Ba1Sm5 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder and 3 mL of 0.3 mol / L sulfuric acid solution were mixed and stirred at room temperature for 1 h for acid treatment. After the treatment, the mixture was filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours to obtain Pt. 0.5 V5-Ba1Sm5 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 powder.
[0061] Example 8 catalyst Pt 0.5 V5-Ba1Sm 15 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 5 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1), 0.5 mL of chloroplatinic acid solution (20 mg / mL), 0.0284 g of barium acetate dihydrate, and 0.765 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared Zr... 0.4 W 0.3 Sm 0.1 Si 0.2 1.57g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550°C for 4 hours to obtain Pt. 0.5 V5-Ba1Sm 15 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder; 2g Pt 0.5 V5-Ba1Sm 15 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2(BaO) powder and 3 mL of 0.3 mol / L sulfuric acid solution were mixed and stirred at room temperature for 1 h for acid treatment. After the treatment, the mixture was filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours to obtain Pt. 0.5 V5-Ba1Sm 15 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 powder.
[0062] Example 9 catalyst Pt 0.5 V5-Ba5Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 5 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1), 0.5 mL of chloroplatinic acid solution (20 mg / mL), 0.142 g of barium acetate dihydrate, and 0.051 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared Zr... 0.4 W 0.3 Sm 0.1 Si 0.2 1.77g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550°C for 4 hours to obtain Pt. 0.5 V5-Ba1Sm 15 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder; 2g Pt 0.5 V5-Ba5Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder and 15 mL of 0.3 mol / L sulfuric acid solution were mixed and stirred at room temperature for 1 h for acid treatment. After the treatment, the mixture was filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours to obtain Pt. 0.5 V5-Ba5Sm1 / Zr 0.4 W 0.3 Sm0.1 Si 0.2 powder.
[0063] Example 10 catalyst Pt 0.5 V5-Ba5Sm5 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 5 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1), 0.5 mL of chloroplatinic acid solution (20 mg / mL), 0.142 g of barium acetate dihydrate, and 0.255 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared Zr... 0.4 W 0.3 Sm 0.1 Si 0.2 1.69g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550°C for 4 hours to obtain Pt. 0.5 V5-Ba5Sm5 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder; 2g Pt 0.5 V5-Ba5Sm5 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder and 15 mL of 0.3 mol / L sulfuric acid solution were mixed and stirred at room temperature for 1 h for acid treatment. After the treatment, the mixture was filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours to obtain Pt. 0.5 V5-Ba5Sm5 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 powder.
[0064] Example 11 catalyst Pt 0.5 V5-Ba5Sm 15 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 5 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1), 0.5 mL of chloroplatinic acid solution (20 mg / mL), 0.142 g of barium acetate dihydrate, and 0.765 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared Zr... 0.4 W 0.3 Sm 0.1 Si 0.2 1.49g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550°C for 4 hours to obtain Pt. 0.5 V5-Ba5Sm 15 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder; 2g Pt 0.5 V5-Ba5Sm 15 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder and 15 mL of 0.3 mol / L sulfuric acid solution were mixed and stirred at room temperature for 1 h for acid treatment. After the treatment, the mixture was filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours to obtain Pt. 0.5 V5-Ba5Sm 15 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 powder.
[0065] Example 12 catalyst Pt 0.5 V5-Ba 15 Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 5 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1), 0.5 mL of chloroplatinic acid solution (20 mg / mL), 0.426 g of barium acetate dihydrate, and 0.051 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared Zr... 0.4 W0.3 Sm 0.1 Si 0.2 1.57g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550°C for 4 hours to obtain Pt. 0.5 V5-Ba 15 Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder; 2g Pt 0.5 V5-Ba 15 Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder and 45 mL of 0.3 mol / L sulfuric acid solution were mixed and stirred at room temperature for 1 h for acid treatment. After the treatment, the mixture was filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours to obtain Pt. 0.5 V5-Ba 15 Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 powder.
[0066] Example 13 catalyst Pt 0.5 V5-Ba 15 Sm5 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 5 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1), 0.5 mL of chloroplatinic acid solution (20 mg / mL), 0.426 g of barium acetate dihydrate, and 0.255 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared Zr... 0.4 W 0.3 Sm 0.1 Si 0.2 1.49g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550°C for 4 hours to obtain Pt.0.5 V3-Ba 15 Sm5 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder; 2g Pt 0.5 V5-Ba 15 Sm5 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder and 45 mL of 0.3 mol / L sulfuric acid solution were mixed and stirred at room temperature for 1 h for acid treatment. After the treatment, the mixture was filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours to obtain Pt. 0.5 V5-Ba 15 Sm5 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 powder.
[0067] Example 14 catalyst Pt 0.5 V5-Ba 15 Sm 15 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 5 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1), 0.5 mL of chloroplatinic acid solution (20 mg / mL), 0.426 g of barium acetate dihydrate, and 0.765 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared Zr... 0.4 W 0.3 Sm 0.1 Si 0.2 1.29g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550°C for 4 hours to obtain Pt. 0.5 V5-Ba 15 Sm 15 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder; 2g Pt0.5 V5-Ba 15 Sm 15 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder and 45 mL of 0.3 mol / L sulfuric acid solution were mixed and stirred at room temperature for 1 h for acid treatment. After the treatment, the mixture was filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours to obtain Pt. 0.5 V5-Ba 15 Sm 15 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 powder.
[0068] Comparative Example 1 catalyst Pt 0.5 V5 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 5 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1) and 0.5 mL of a chloroplatinic acid solution (20 mg / mL) to 1.5 mL of deionized water and stir until homogeneous. Then add the prepared Zr... 0.4 W 0.3 Sm 0.1 Si 0.2 1.89 g of powder was stirred evenly and then allowed to stand at room temperature for 1.5 h, stirred at 40 °C for 1 h, stirred at 50 °C for 1 h, and stirred at 60 °C for 1 h in sequence. The mixture was then dried at 80 °C for 15 h. The dried mixture was then calcined at 550 °C for 4 h to obtain Pt. 0.5 V5 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 powder.
[0069] Comparative Example 2 catalyst Pt 0.5 -Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 Preparation: Add 0.5 mL of 20 mg / mL chloroplatinic acid solution, 0.0284 g of barium acetate dihydrate, and 0.051 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared Zr... 0.4 W 0.3 Sm 0.1 Si 0.2 1.95g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550°C for 4 hours to obtain Pt. 0.5 -Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 (BaO) powder; 2g Pt 0.5 -Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 BaO powder was mixed with 3 mL of 0.3 mol / L sulfuric acid solution and stirred at room temperature for 1 h for acid treatment. After treatment, the mixture was filtered and washed twice with deionized water to obtain a precipitate. The precipitate was dried at 80 °C for 15 h to obtain Pt. 0.5 -Ba1Sm1 / Zr 0.4 W 0.3 Sm 0.1 Si 0.2 powder.
[0070] Comparative Example 3 catalyst Pt 0.5 V5-Ba1Sm1 / Zr 0.5 W 0.3 Si 0.2 Preparation: Add 5 mL of a vanadium metavanadate complex solution (25.7 mg / mL, molar ratio of oxalic acid dihydrate to ammonium metavanadate 3:1), 0.5 mL of chloroplatinic acid solution (20 mg / mL), 0.0284 g of barium acetate dihydrate, and 0.051 g of samarium nitrate pentahydrate to 1.5 mL of deionized water and stir to dissolve. Then add the prepared comparative support Zr to the mixed solution. 0.5 W 0.3 Si 0.2 1.89g of powder was stirred evenly and then allowed to stand at room temperature for 1.5h, stirred at 40℃ for 1h, stirred at 50℃ for 1h, stirred at 60℃ for 1h, and then dried at 80℃ for 15h. The dried mixture was calcined at 550°C for 4 hours to obtain Pt.0.5 V5-Ba1Sm1 / Zr 0.5 W 0.3 Si 0.2 (BaO) powder; 2g Pt 0.5 V5-Ba1Sm1 / Zr 0.5 W 0.3 Si 0.2 (BaO) powder and 3 mL of 0.3 mol / L sulfuric acid solution were mixed and stirred at room temperature for 1 h for acid treatment. After the treatment, the mixture was filtered and washed twice with deionized water to obtain the precipitate. The precipitate was dried at 80°C for 15 hours to obtain Pt. 0.5 V5-Ba1Sm1 / Zr 0.5 W 0.3 Si 0.2 powder.
[0071] Weigh 0.1 g of the catalysts prepared in Examples 1-14 and Comparative Examples 1-3 of this invention, grind and compress them into tablets, and then sieve 40-60 mesh catalyst particles for testing. The test was conducted in a fixed-bed reactor to investigate the catalytic activity and sulfur poisoning resistance of the catalysts in the CO catalytic combustion reaction, with a space velocity of 20000 mL·g⁻¹. -1 ·h -1 The temperature window for activity testing is 150~300℃; the volume composition of the CO reaction gas is: 0.5% CO, 5 vol% O2, N2 as balance gas, and 3000 ppm SO2.
[0072] Table 1. Composition of catalysts prepared in Examples 1-14 and Comparative Examples 1-3 and CO removal test results.
[0073] Table 1 lists the catalyst activities using T. 90 The temperature at which CO conversion reaches 90% is indicated in Table 1. 90 [1] "This refers to the results obtained under an atmosphere free of SO2." Table 1 shows the "CO conversion rate after 200 hours of reaction under an SO2 atmosphere." [2] "This refers to the T value of the catalyst" 90 The mixture was obtained after reacting with a reaction gas and a 3000ppm SO2 mixture at a certain temperature for 200 hours.
[0074] Table 1 shows that the catalyst provided by this invention has good catalytic effect on CO catalytic combustion. The test results of Examples 1-6 show that the catalytic activity is best when the Pt content is 0.5 wt% and the V₂O₅ content is 5 wt% (while also considering T). 90(and sulfur resistance stability), therefore, with a fixed Pt content of 0.5 wt% and a V2O5 content of 5 wt%, the catalytic combustion activity of catalysts with different co-catalyst contents (Examples 7-14) was evaluated.
[0075] As can be seen from the test results of Examples 6-14 in Table 1, the prepared catalyst was simultaneously loaded with two co-catalysts, BaSO4 and Sm2O3. When the content of BaSO4 was 1wt%~15wt% and the content of Sm2O3 was 1wt%~15wt%, the catalyst had stronger resistance to high sulfur, indicating that the CO catalytic combustion catalyst with high sulfur resistance provided by the present invention has good catalytic activity and excellent resistance to high sulfur.
[0076] Furthermore, the test results of Comparative Examples 1-3 in Table 1 show that after 200 h of reaction in Comparative Example 1 (without co-catalyst), the CO conversion rate was only 65%, far lower than that of the example samples containing co-catalysts (which could reach up to 90%). This indicates that the introduction of co-catalysts BaSO4 and Sm2O3 is crucial for improving the catalyst's resistance to high sulfur. Comparative Example 2 (without V2O5 active component) showed a T... 90 At a temperature as high as 260℃, the CO conversion rate was only 68%, indicating that the addition of V2O5 can significantly reduce the ignition temperature of CO catalytic combustion and form an effective synergistic catalytic effect with Pt. Comparative Example 3 (support without Sm2O3 component) T 90 At 258℃, after 200 hours, the CO conversion rate was 70%, significantly lower than that achieved using the Zr of this invention. 0.4 W 0.3 Sm 0.1 Si 0.2 Examples of quaternary composite oxide supports (such as Example 6, T) 90 (At 235℃, the conversion rate was 80% after 200 hours), demonstrating that the introduction of the Sm2O3 component in the support plays a positive role in optimizing the acidity and redox performance of the support and improving the overall sulfur resistance of the catalyst. The above comparative examples further verify the synergistic effect of the "quaternary composite oxide support + Pt / V2O5 dual active component + BaSO4 / Sm2O3 composite co-catalyst" technical solution of this invention and the importance of each component being indispensable.
[0077] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A high-sulfur-resistant CO catalytic combustion catalyst, characterized in that, It includes a strongly acidic support, an active component supported in the porous structure of the strongly acidic support, and a co-catalyst; The cocatalyst includes BaSO4 and Sm2O3; the active component is a composite active component of Pt and V2O5; the strong acid support is a ZrO2-WO3-Sm2O3-SiO2 quaternary composite oxide; The total mass of the active components Pt and V2O5 is 1-8% of the mass of the CO catalytic combustion catalyst.
2. The CO catalytic combustion catalyst as described in claim 1, characterized in that, The content of the strong acid support is 60-89% by mass percentage, the content of the co-catalyst is 2-35%, the content of the active component is 1-10%, and the sum of the mass percentages of the strong acid support, co-catalyst, and active component is 100%.
3. The CO catalytic combustion catalyst according to claim 1, characterized in that, In the ZrO2-WO3-Sm2O3-SiO2 quaternary composite oxide, the mass content of ZrO2 is 30~50%, the mass content of WO3 is 20~40%, the mass content of Sm2O3 is 5~20%, and the mass content of SiO2 is 10~30%; the mass ratio of Pt to V2O5 in the active component is (0.1~1):(1~5).
4. The CO catalytic combustion catalyst as described in claim 1, characterized in that, The particle size of the CO catalytic combustion catalyst is 20-80 mesh.
5. A method for preparing the CO catalytic combustion catalyst according to any one of claims 1 to 4, comprising the following steps: (1) After mixing zirconium source, tungsten source, samarium source, silicon source, alcohol solvent and precipitant, the pH value of the resulting mixture was adjusted to 10~11 for the first deposition, aging and first calcination to obtain ZrO2-WO3-Sm2O3-SiO2 composite oxide; (2) The ZrO2-WO3-Sm2O3-SiO2 composite oxide, the aqueous solution of the active component precursor and the aqueous solution of the co-catalyst precursor are mixed and then allowed to stand, heated and mixed in the Ath, Bth, Cth and Dth stages, and then calcined to obtain the catalyst supported on the active component. (3) The supported active component catalyst and the acid solution are mixed and acid-treated to obtain a high-sulfur CO catalytic combustion catalyst.
6. The preparation method according to claim 5, characterized in that, The zirconium source is zirconium nitrate; the tungsten source is ammonium metatungstate; the samarium source is samarium nitrate; the silicon source is tetraethyl orthosilicate; the alcohol solvent is anhydrous ethanol; the first deposition temperature is room temperature and the time is 1 hour; the aging temperature is 70~90℃ and the holding time is 5~7 hours; the first calcination temperature is 500~600℃ and the holding time is 3~5 hours.
7. The preparation method according to claim 5, characterized in that, The active component precursor includes chloroplatinic acid and / or vanadium oxalate complex; the vanadium oxalate complex is a mixed solution of oxalic acid dihydrate and ammonium metavanadate; the molar ratio of oxalic acid dihydrate to ammonium metavanadate in the mixed solution of oxalic acid dihydrate and ammonium metavanadate is 2~4:1; the cocatalyst precursor includes barium acetate dihydrate and samarium nitrate.
8. The preparation method according to claim 5, characterized in that, The settling temperature is room temperature, and the time is 1~2 hours; The heating and mixing method for the Ath heating method is heating and stirring; the heating and stirring temperature for the Ath heating and mixing is 35~45℃, the time is 0.5~1.5h, and the stirring speed is 50~150r / min; The heating and mixing method for the Bth heating and mixing is heating and stirring; the heating and stirring temperature for the Bth heating and mixing is 45~55℃; the stirring time is 0.5~1.5h; and the stirring speed is 50~150r / min. The Cth heating and mixing method is heating and stirring; the heating and stirring temperature of the Cth heating and mixing is 55~65℃, the stirring time is 0.5~1.5h, and the stirring speed is 50~150r / min; The heating and mixing method for the Dth heating and mixing is heating and stirring; the heating and stirring temperature for the Dth heating and mixing is 65~75℃, the stirring time is 0.5~1.5h, and the stirring speed is 50~150r / min; The second roasting temperature is 500~600℃, and the holding time is 3~5h.
9. The application of the CO catalytic combustion catalyst according to any one of claims 1 to 4 or the high-sulfur resistant CO catalytic combustion catalyst prepared by the preparation method according to any one of claims 5 to 8 in CO catalytic combustion.
10. The application as described in claim 9, characterized in that, During the catalytic combustion of CO, the volume concentration of SO2 in the CO reaction gas is ≥1000ppm.
Citation Information
Patent Citations
Monolithic medium and low temperature water-resistant sulfur-resistant CO oxidation catalyst and preparation method thereof
CN117085678A